1997
DOI: 10.1016/s1055-3290(97)80040-4
|View full text |Cite
|
Sign up to set email alerts
|

Social support for HIV-infected mothers: Relation to HIV care seeking

Abstract: A cross-sectional survey was conducted to identify sources of social support for 92 HIV-seropositive mothers and to examine the relationship between social support and initiation of health care after a positive test for HIV antibody. Main outcome measures were self-reported source and amount of social support and length of time between the first positive HIV antibody test and the first visit for HIV care. Results indicated that HIV-infected mothers frequently delay seeking medical care and report attenuated so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In some of these studies, social support was associated with clinic attendance (Waldrop-Valverde, Guo, Ownby, Rodriguez, & Jones, 2014) and delayed time to care (McCoy et al, 2009). In other studies, there were no significant relationships of social support with ART adherence (Sagarduy, Lopez, Remirez, & Davila, 2017), entry into care (Williams, Shahryarinejad, Andrews, & Alcabes, 1997), viral load or ART adherence (Attonito, Devieux, Lerner, Hospital, & Rosenberg, 2014;Safren et al, 2014). However, in the Friedman et al (2017) study, social support was associated negatively with viral load and in the work of Leserman et al (2002), less social support predicted HIV disease progression.…”
Section: Associations Between Resilience Resources and Hiv-related Oumentioning
confidence: 97%
“…In some of these studies, social support was associated with clinic attendance (Waldrop-Valverde, Guo, Ownby, Rodriguez, & Jones, 2014) and delayed time to care (McCoy et al, 2009). In other studies, there were no significant relationships of social support with ART adherence (Sagarduy, Lopez, Remirez, & Davila, 2017), entry into care (Williams, Shahryarinejad, Andrews, & Alcabes, 1997), viral load or ART adherence (Attonito, Devieux, Lerner, Hospital, & Rosenberg, 2014;Safren et al, 2014). However, in the Friedman et al (2017) study, social support was associated negatively with viral load and in the work of Leserman et al (2002), less social support predicted HIV disease progression.…”
Section: Associations Between Resilience Resources and Hiv-related Oumentioning
confidence: 97%
“…Williams et al (1997) found that women (n = 92) in their study relied on young children for comfort. Women in the study by Butz et al (1993) said they did not keep appointments because they feared being identified at the clinic, dreaded the prolonged waiting periods for first appointments, and were constrained by priorities such as drug use or pursuit of financial and housing assistance.…”
Section: Review Of the Literaturementioning
confidence: 90%
“…As women continue to be one of the ranking subgroups infected and affected by HIV disease (Williams, Shahryaniejad, & Andrews, 1997), they bring with them experiences and needs quite different from the needs of other populations. Many are mothers concerned about who will provide for and take care of their children if they die (Hackl, Somlai, Kelly, & Kalichman, 1997).…”
mentioning
confidence: 99%
“…Fear of disclosure has been found in other work among HIV-positive women. 28,29 However, one caveat in the potential for health care to mitigate barriers to prenatal care is the discrimination and stigmatization experienced by these women. Discrimination in the health care system against HIVinfected women, including inappropriate infection control practices and concerns related to confidentiality, has been documented elsewhere.…”
Section: Discussionmentioning
confidence: 99%